2015
DOI: 10.1007/s11676-015-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil-nitrogen net mineralization increased after nearly six years of continuous nitrogen additions in a subtropical bamboo ecosystem

Abstract: In order to understand the effects of increasing atmospheric nitrogen (N) deposition on the subtropical bamboo ecosystem, a nearly six-year field experiment was conducted in a Pleioblastus amarus plantation in the rainy region of SW China, near the western edge of Sichuan Basin. Four N treatment levels-control (no N added), low-N (50 kg N ha -1 a -1 ), medium-N (150 kg N ha -1 a -1 ), and high-N (300 kg N ha -1 a -1 )-were applied monthly in the P. amarus plantation starting in November 2007. In June 2012, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Nitrogen addition was associated with heightened soil NH 4 + concentration, which can be expected to accelerate nitrification 6, 43 . This is because NH 4 + is the substrate of nitrification and the nitrification rate depends on soil NH 4 + concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen addition was associated with heightened soil NH 4 + concentration, which can be expected to accelerate nitrification 6, 43 . This is because NH 4 + is the substrate of nitrification and the nitrification rate depends on soil NH 4 + concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that N deposition can result in soil acidification in terrestrial ecosystems 15 , 28 , 29 , 48 , which was confirmed by our study. Nitrogen addition was associated with heightened soil NH 4 + concentration, which can be expected to accelerate nitrification 6 , 43 . This is because NH 4 + is the substrate of nitrification and the nitrification rate depends on soil NH 4 + concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, soil net N mineralization (SNmin) includes net mineralization (Nmin, inorganic N), net nitrification (NNmin, NO 3 --N)), and net ammonification (ANmin, NH 4 + -N). The Nmin, NNmin, and ANmin as the difference between planting and harvest (end-start) in soil [48,49]. All values were standard transformed using the min-max normalization method to satisfy the requirements of normality and homogeneity of variance.…”
Section: Calculation and Statisticsmentioning
confidence: 99%
“…Overall, Nmin, ANmin, and NNmin were not only suppressed by environmental factors, but also were affected by the enzyme and pH, which may even relate to N-fixing bacteria [30]. The previous study showed that ANmin and NNmin were significantly influenced by soil moisture and root biomass [49], and a significant positive correlation was also found between Nmin and fine-root biomass [48]. It was reported that the increase in fine-root biomass can lead to the increase of rootderived C, which is coupled with stimulating microbial activity and accelerating N transformation in the soils [79], even affecting the C:N soil [80].…”
Section: The Mechanism Of Soil Net N Mineralizationmentioning
confidence: 99%